Tibiofemoral bony morphology features associated with ACL injury and sex utilizing three‐dimensional statistical shape modeling - Polamalu, Sene K.; Musahl, Volker; Debski, Richard E. (Journal of orthopaedic research, 2022)
Statistical shape modeling was employed to assess three‐dimensional (3D) bony morphology between distal femurs and proximal tibiae of anterior cruciate ligament (ACL) injured knees, the contralateral uninjured knees of ACL injured subjects, and knees with no history of injury. Surface models were created by segmenting bone from bilateral computed‐tomography scans of 20 subjects of their ACL injured knees and non‐injured contralateral knees, and 20 knees of control subjects with no history of a knee injury. Correspondence particles were placed on each surface, and a principal component analysis determined modes of variation in the positions of the correspondence particles describing anatomical variation. ANOVAs assessed the statistical differences of 3D bony morphological features with main effects of injury state and sex. ACL injured knees were determined to have a more lateral femoral mechanical axis and a greater angle between the long axis and condylar axis of the femur. A smaller anterior–posterior dimension of the lateral tibial plateau was also associated with ACL injured knees. Results of this study demonstrate that there are more bony morphological features predisposing individuals for ACL injury than previously established. These bony morphological parameters may cause greater internal and valgus torques increasing stresses in the ACL. No differences were determined between the ACL injured knees and their uninjured contralateral knees demonstrating that knees of ACL injured individuals are at similar risk for injury. Further understanding of the effect of bony morphology on the risk for ACL injury could improve individualized ACL injury treatment and prevention.